Explanatory and Confirmatory The Teachings of the Apostle Paul about Preach the Gospel Based on 1 Thessalonians 2:1-12 Among the Beth-el Tabernacle Church Congregation in Boyolali Regency - Wahyuni, Sri; Roy, Gidion Willy; Daliman, Muner (Jurnal Pendidikan Agama Kristen (JUPAK), 2023)
Preaching the Gospel is the great commission of the Lord Jesus and Christians are obliged to carry it out, but in reality there are still many Christians who have not preached the gospel, the reason is that there are many challenges that must be faced. The Apostle Paul gave a good effort in 1 Thessalonians 2:1-12 in preaching the gospel therefore, this study aims to determine the level, dominant dimension and dominant background in determining the confirmation of the Apostle Paul's teaching about preaching the gospel based on 1 Thessalonians 2: 1-12 among members of the Beth-el Tabernacle Church in Boyolali district. This study uses quantitative methods, data obtained from library sources and distributed questionnaires. The results show that the level of confirmation of the Apostle Paul's teaching about preaching the gospel based on 1 Thessalonians 2:1-12 among the Beth-el Tabernacle Church congregations in Boyolali district is in the medium category, the dominant dimension determines the level of confirmation of the Apostle Paul's teaching about preaching the gospel based on 1 Thessalonians 2:1-12 among the Beth-el Tabernacle Church congregations in Boyolali district is the commitment to preach the gospel and the most dominant background determines the level of confirmation of the Apostle Paul's teaching about preaching the gospel based on 1 Thessalonians 2:1-12 among the Beth-el Church congregations. el Tabernacle in Boyolali Regency is the length of time he has been a congregation.